Cost Effectiveness of TNF-α Inhibitors in Rheumatoid Arthritis. (13th November 2013) - Said, Cynthia; Coleiro, Bernard; Zarb Adami, Maurice; Azzopardi, Lilian M.; Serracino Inglott, Anthony
Abstract : Background. TNF-α inhibitors have shown to be effective in reducing disease activity and improving the quality of life. Due to the high costs associated with acquisition of this treatment, this study was undertaken to evaluate the ICER of TNF-α antagonists (etanercept, adalimumab, and infliximab) in improving the quality of life. Methods. The HAQ and SF-36 were administered at phases 1, 2, and 3, in order to assess the improvement in the QOL. Suppression of disease activity was assessed through the DAS-28. Results. Statistically significant improvements (P < 0.05 ) were noted for the SF-36 and HAQ after 3 months and for the DAS-28 after 6 months of TNF-α inhibitor therapy. The mean ICER per 10% improvement in the HAQ, DAS-28, and SF-6D were €1976.5, €2086.5, and €2316.4, respectively, following 6 months of TNF-α intervention. Most favorable ICERs were reported from a patient who had to undergo surgical intervention whilst on DMARD therapy. Conclusion. Significant improvement was observed in patients' quality of life, after a short timeframe of 6 months. Such data is useful information in the light of convincing policy makers, in terms of providing access to the medications to individual patients on national health service schemes.